NANOSTRUCTURAL COVERINGS ON THE BASIS OF BINARY ALLOYS OF ALUMINIUM - Jurov, V.M.; Ibraev, N. H.; Guchenko, S. A. (Recent Contributions to Physics, 2018)
In work results of research of composite coverings on the basis of aluminium alloys are resulted. The quantitative analysis of element structure of composite coverings was spent on electronic microscope JEOL JSM-5910. By mathematical processing of power spectra under special program PHI-RHO-Z concentration of elements have been defined researches of a microstructure of composite coverings by a method of the atomno-power microscopy, combining modes of topography and phase contrast are carried out. The information about the mechanism of local deformation of a covering is received.